The slave family in Bourbon - (:unkn) unknown (My University, 2011)
From the end of the 17th century until the abolition of 1848, Bourbon Island in the South-West Indian Ocean, saw a slave system marked by consolidation and practices of different authorities downgrading or denied family structures of the slave. Next to other means of servile resistors as the "marronage" or revolt, it appears through the reconstruction of slaves families, these forms of organization have enabled a population from raids in Africa or Madagascar, then strongly creolized regain his humanity, investing field of kinship that civil or religious powers denied. If a small number of families were recognized at the time of the India Company, the majority of slaves lived in Maroon families, ignored and disregarded. They will appear in broad daylight after the abolition of slavery in 1848. The birth rate was important in the group of slaves but accompanied by a high infant mortality. Privileged place of cultural and linguistic values transmissions, slave family, in all forms, has helped many slaves to survived to an inhuman system, those excludes from the kinship system mostly belonging to the groups have experienced the destruction of their family system in Africa or Madagascar.
Keywords: African Research